Sero-prevalence of brucellosis (Brucella abortus) in bovines from Caquetá state, Colombia - Motta-Delgado, Pablo Andrés; Martínez-Tovar, Ricardo Alberto; Londoño-Giraldo, Marliyanini; Rojas-Vargas, Erika Paola; Herrera-Valencia, Wilmer (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Brucellosis is a disease with implications in the public health due both to its zoonotic character as its easy transmission trough of dairy products contaminated with the microorganism Brucella sp.  The aim of this article was determinate the prevalence of bovine brucellosis in nine municipalities that carrying the 75% of bovine population in the Caquetá state, Colombia. Blood samples were collected in 100 herds dedicates to dual-purpose cattle, obtained blood serum from 1000 animals, of which 882 corresponding to cows. Rose Bengal Plate Test was performed and the confirmations of positive cases were made by competitive Elisa. The sero-prevalence of bovine brucellosis in Caquetá state was of 3.23% (95%, CI: 0-6.53%), in males 2.6% and females 3.29% respectively. At the municipal level, the sero-prevalence varied of 0 to 6.06%. The prevalence of brucellosis at herd level was of 22% (95%, CI: 12.24-31.76%). In conclusion, the sero-prevalence is low in bovines but moderate at the level of herds, therefore, it is necessary to increase the performance of the official control entities at the level of herds to reduce the high prevalence of the disease for guaranteed the safety of milk and thus the health of consumers.